2009
DOI: 10.1111/j.1469-1809.2009.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Structure of the Y‐chromosomal Genetic Landscape of the Levant: A coastal‐inland contrast

Abstract: SUMMARYWe have examined the male-specific phylogeography of the Levant and its surroundings by analyzing Y-chromosomal haplogroup distributions using 5874 samples (885 new) from 23 countries. The diversity within some of these haplogroups was also examined. The Levantine populations showed clustering in SNP and STR analyses when considered against a broad Middle-East and North African background. However, we also found a coastal-inland, east-west pattern of diversity and frequency distribution in several haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 48 publications
0
39
1
Order By: Relevance
“…It has been reported that Muslim expansion from the Arabian Peninsula during the 7th century lead to the current Lebanese Muslims. The Crusaders in the 11th-13th centuries introduced European lineages to already existing Lebanese Christians who have inhabited the eastern coast of the Mediterranean area and the nearby Mount Lebanon since the early onset of Christianity (Zalloua et al, 2008;El-Sibai et al, 2009). Most of our research participants were Muslims who constitute the majority of the AUBMC neighborhood; therefore, our results may reflect the effect of the immigration of Muslims from the Arabian Peninsula to both Lebanon and Egypt.…”
Section: Frequency Distributionmentioning
confidence: 77%
“…It has been reported that Muslim expansion from the Arabian Peninsula during the 7th century lead to the current Lebanese Muslims. The Crusaders in the 11th-13th centuries introduced European lineages to already existing Lebanese Christians who have inhabited the eastern coast of the Mediterranean area and the nearby Mount Lebanon since the early onset of Christianity (Zalloua et al, 2008;El-Sibai et al, 2009). Most of our research participants were Muslims who constitute the majority of the AUBMC neighborhood; therefore, our results may reflect the effect of the immigration of Muslims from the Arabian Peninsula to both Lebanon and Egypt.…”
Section: Frequency Distributionmentioning
confidence: 77%
“…Molecular genetic analyses of modern human populations provided important clues to reconstruct the past migratory trajectories in the eastern Mediterranean and Anatolia. 2,[20][21][22][23][24] Nevertheless, these results are limited by the fact that various demographic events could have obscured over time the evolutionary history inferred from modern populations. In this context, genetic analysis of ancient populations appears to be a promising way to investigate the origin of human populations and to validate hypotheses based on modern genetic data and other fields of study (eg historical and archaeological data).…”
Section: Introductionmentioning
confidence: 98%
“…Three out of five haplotypes fully matched with a total of 76 chromosomes of Albanian (31.6%), Balkan (30.3%), Central European (28.9%), Italian (1.3%) but also North African (5.3%) origin. Whether the African matches (two haplotypes from Sohag, Egypt; one haplotype from El Minia, Egypt; two haplotypes from Sfax, Tunisia) are identical by descent to Jevg chromosomes or they are the effect of convergence, a phenomenon commonly observed among haplotypes belonging to E-M35 subgroups [36] could be checked only by typing a larger set of population samples for M35 downstream mutations.…”
Section: Y-snp Variationmentioning
confidence: 99%